Epidemiology of cutaneous sarcoidosis, 1976–2013: a population‐based study from Olmsted County, Minnesota. (21st June 2016) - Ungprasert, P.; Wetter, D.A.; Crowson, C.S.; Matteson, E.L.
Abstract: Background: The epidemiology of cutaneous sarcoidosis is not well‐characterized as only referral‐based studies are available. Objectives: To characterize the epidemiology of cutaneous sarcoidosis, with emphasis on annual incidence and clinical characteristics, from 1976 to 2013. Methods: Inception cohorts of patients with incident isolated cutaneous sarcoidosis and incident systemic sarcoidosis with cutaneous involvement in 1976–2013 in Olmsted County, Minnesota, United States were identified based on comprehensive individual medical record review. Inclusion in the isolated cutaneous sarcoidosis cohort required physician diagnosis and skin biopsy showing non‐necrotizing granuloma. Inclusion in the systemic sarcoidosis with cutaneous involvement cohort required presence of systemic sarcoidosis and cutaneous lesions. Presence of systemic sarcoidosis was determined by physician diagnosis supported by histopathology of non‐necrotizing granuloma, characteristic radiologic features of intrathoracic sarcoidosis and exclusion of other granulomatous diseases. Cutaneous lesions were defined as either sarcoidosis‐specific or non‐specific. Results: There were 62 cases with sarcoidosis‐specific cutaneous lesions (36 cases of sarcoidosis‐specific cutaneous lesions and 26 cases of isolated cutaneous sarcoidosis) which corresponded to an incidence of 1.9 per 100 000 population. The female to male ratio was 2.1 : 1. Plaques, papules and subcutaneous nodules were the most commonly observed cutaneous lesions. There was no significant difference in cutaneous presentation between those who had isolated skin disease and those who had skin disease in association with systemic sarcoidosis. Prognosis of cutaneous sarcoidosis was favourable, as over 90% of patients had a good response to either glucocorticoids, hydroxychloroquine or tetracycline antibiotics. This study has a significant limitation, in that the studied population was predominantly Caucasians who generally have a lower prevalence of skin disease. Conclusions: The incidence of sarcoidosis‐specific cutaneous lesions was about 1.9 per 100 000 population with female predominance. The cutaneous presentations were similar among those with and without systemic sarcoidosis.